PENGARUH ARUS KAS BEBAS, PROFITABILITAS, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP KEBIJAKAN HUTANG - Halim, Kusuma Indawati; Novianty, Novianty (LPPM Universitas Bina Bangsa, 2023)
The company's management has a responsibility in determining the funding of the company's activities while being able to fulfill its obligations. This study aims to examine the effect of free cash flow, profitability, and institutional ownership on debt policy. The variable free cash flow is measured by the amount of cash available from operating activities after paying off capital expenditures, the profitability variable is measured by the return on assets ratio, the institutional ownership variable is measured by dividing the number of shares owned by the institution by the number of outstanding shares, and the debt policy variable is measured by the debt to assets ratio. The form of this research is an associative study. The total population is 58 property and real estate sub-sector companies on the Indonesia Stock Exchange. The determination of the research sample used a purposive sampling method and obtained a sample of 34 sample companies. The data analysis technique uses panel data regression. Processing data in research using Eviews 12. Based on the test results, it is known that free cash flow has a positive effect on debt policy, profitability has no effect on debt policy, and institutional ownership has a negative effect on debt policy